Analysis of Water Quality in the Riverside Residential Area of the Kahayan River, Palangka Raya - Astoeti, Dileli Dharma; Tjahjono, Herry; Toemon, Angeline Novia (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
The Kahayan River plays an important role in the lives of the people of Palangka Raya City, particularly for residents living in riverside areas. The high dependence on the river, without being balanced by adequate sanitation systems and spatial planning, has caused various environmental and health problems, such as increased cases of diarrhea and digestive disorders. This study aims to evaluate the water quality of the Kahayan River using rapid assessment methods with a quantitative approach through laboratory testing. Sampling was conducted at three locations: Tumbang Rungan, Pahandut Seberang, and Bereng Bengkel. Analysis was performed on physicochemical parameters (temperature, pH, BOD, COD, and iron content) as well as microbiological parameters (number of E. coli bacteria). Results show that all water samples do not meet drinking water quality standards based on PP No. 22 of 2021. Low pH and high levels of COD and E. coli, particularly in Pahandut Seberang, reflect domestic waste pollution. Conversely, lower COD and BOD values in Bereng Bengkel indicate natural dilution processes. Based on these findings, efforts to improve sanitation infrastructure, change community behavior towards clean living, and optimize waste management are needed to reduce health risks from water pollution in Kahayan riverside settlement areas.